Vortex Trajectory of Rotating Shaft Undergoing Vibration Coupling of Parallel Multicylinders - Ben Zhang; Yu Li; Zhong Tang; Hao Zhang; Yaquan Liang; Zhan Su (Advances in Materials Science and Engineering)
Multiple threshing cylinders of combine harvester are mainly driven in parallel, whose transmission methods are complex causing the excitations coupled with each other. The mutual excitation coupling of multiple threshing cylinders causes a severe vibration state of the combine harvester with poor stability. In order to analyze the influence of transmission system coupling on the unbalanced response of the parallel multicylinder system, this paper established a mathematical model of the parallel multicylinder system and derived the general vortex trajectory expression of the unbalanced response of threshing cylinder shaft undergoing vibration coupling of parallel multicylinders. Vibration tests of the bearing seat and the rotating shaft were carried out for comparison and verification. Results showed that the existence of the transmission chain and the transmission mode cause the boundary conditions of the multicylinder system to change, which ultimately led to changes in the unbalanced response of the transmission system. The contribution rate of different transmission methods and rotation speeds to the vibration amount at the fundamental frequency of the multicylinder was 5% to 30%. The existence of the transmission system caused the vibrations of the various units to be coupled with each other, mutually transmitted, and superimposed, leading to changes in the vortex shape of the rotating shaft and the unbalanced response of the transmission system.